2016
DOI: 10.1111/jth.13476
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of red blood cell transfusion utilization between anti‐activated factor X and activated partial thromboplastin monitoring in patients receiving unfractionated heparin

Abstract: Anti‐activated factor X (Anti‐Xa) monitoring is more precise than activated partial thromboplastin (aPTT). 20 804 hospitalized cardiovascular patients monitored with Anti‐Xa or aPTT were analyzed. Adjusted transfusion rates were significantly lower for patients monitored with Anti‐Xa. Adoption of Anti‐Xa protocols could reduce transfusions among cardiovascular patients in the US. Summary BackgroundAnticoagulant activated factor X protein (Anti‐Xa) has been shown to be a more precise monitoring tool than act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Vizient is an administrative patient-level database which includes inpatient and hospital-based outpatient information from more than 400 hospitals across 42 US states (59% Southern, 17% Western, 13% Midwestern, 12% Northeastern region). 12 Hospitals included large and small facilities in urban (87%) and rural (13%) locations. Inpatient and outpatient data are submitted by ~98% of providers, and data are updated twice monthly with a 30-to-45-day lag from month-end.…”
Section: Data Sourcementioning
confidence: 99%
“…Vizient is an administrative patient-level database which includes inpatient and hospital-based outpatient information from more than 400 hospitals across 42 US states (59% Southern, 17% Western, 13% Midwestern, 12% Northeastern region). 12 Hospitals included large and small facilities in urban (87%) and rural (13%) locations. Inpatient and outpatient data are submitted by ~98% of providers, and data are updated twice monthly with a 30-to-45-day lag from month-end.…”
Section: Data Sourcementioning
confidence: 99%
“…These studies, which included a small number of patients, were often retrospectively designed, 30‐35 except one single‐center prospective randomized management study aimed at comparing the two monitoring strategies with clinical end‐points in a cohort of 131 patients with VTE 36 . By evaluating various criteria such as the rate of recurrence of thrombosis, the rate of bleeding complication, the time‐to‐therapeutic range, the number of dosage change, the total UFH dosage, the duration or the cost of hospital stay, or even the need for red blood cells transfusion, 37 all concluded that anti‐Xa had at least similar safety/efficacy/efficiency in UFH monitoring when compared to aPTT, even though differences were not always significant partly because of their lack of statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective analysis of more than 22,000 adult medical patients, anti-Xa-based heparin management significantly reduced transfusions when compared to an aPTT-based strategy (23). In a retrospective study of 100 ECMO and non-ECMO children, therapeutic anti-Xa levels were associated with a 66% reduction in the thrombosis rate, while 11% of patients experienced bleeding, particularly when aPTT values were excessive (24).…”
Section: Heparin-concentration Based Monitoring With Anti-xa Assaysmentioning
confidence: 99%
“…Results from pediatric patients are promising, and discounting how far these results can be translated to the adult wards, the fundamental limitations of the observational and single-center nature of these studies have to be clearly considered. Moreover, in ECMO patients with an impaired overall coagulation system, particularly after major surgery, such a strategy may be associated with an increased risk of bleeding (23).…”
Section: Commentsmentioning
confidence: 99%